Field notes contributed by Darwin Koenig, February 13, 1980 - Koenig, Darwinet al (1980)
List of birds and locations contributed by Darwin Koenig, February 13, 1980. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1979-1980. Epson - sheet feed/flatbed